Analisis Kualitas Produk, Kualitas Pelayanan, dan Harga Terhadap Kapuasan Pelanggan Menggunakan Metode Importance Performance Analysis - Ardianto, Ivan; Samanhudi, Didi; Iriani, Iriani (Universitas Hamzanwadi, 2023)
This research was conducted to find out what attributes are the top priority in supporting customer satisfaction at Diqqi's lesehan. These factors include product quality, service quality, and price. Because the population size in this study was unknown, the Bernoulli formula was used to determine the sample size. the sample that will be used to represent the population is a minimum of 100 respondents. Data collection techniques using questionnaires distributed to customers. The data analysis technique uses the Importance Performance Analysis method. The results of this study are that the attributes that are the top priority for improving and improving their performance are those that are in quadrant I because these factors are considered very significant for customers, but their performance has not been able to satisfy customers. Steps that can be taken are to make improvements to boost the quality of performance in this quadrant. The results of this study are expected to provide input for the Diqqi lesehan stall in improving product quality, service quality, and prices in order to increase customer satisfaction.